O impacto da nova arquitetura pública na paisagem da capital paraibana: 1900 - 1950 - Araújo, Darlene Karla (2008)
This dissertation studies the role played by the public architecture produced between 1900 and 1950 at the capital of Paraíba State (Brazil) in the transformation of its townscape occurred between those years. This architecture introduced into the town many public buildings that were much larger and taller than the existing ones and styles that had not been used there yet, such as the academic classicism, the Neocolonial language, the Art Deco and the International Style (the last three, created during the above period). The dissertation examines over forty buildings that contributed to the mentioned transformation; they were both new constructions and the result of works of renovation or extension. Most of these buildings appeared during the 25 years comprised between 1916 and 1940 and many of them were produced by the government as part of its policy to embellish the capital of the State. The transformation of the townscape took place mainly at major squares and along the two main traffic routes of the town, one stretching from the north to the south and the other from the east to the west.